Self‐Organization of Remote Reservoirs: Transferring Computation to Spatially Distant Locations. (3rd December 2021) - Tanaka, Kazutoshi; Tokudome, Yuji; Minami, Yuna; Honda, Satoko; Nakajima, Toshiki; Takei, Kuniharu; Nakajima, Kohei
Abstract : Soft materials generate rich and diverse dynamics that can be used as computational resources based on the framework of physical reservoir computing. Herein, a method that exploits the dynamic coupling between soft structures and a water medium to allow for the transfer of computation to spatially distant locations is proposed. This technique is implemented by introducing the concept of remote reservoirs that can autonomously alter their physical constituents in real time rather than using reservoirs with predefined, fixed physical constituents. These remote reservoirs self‐organize by including many ad hoc physical substrates in the environment, making the framework more flexible for soft robotic applications. Using a simple experimental platform consisting of silicone rubber strips containing embedded flexible strain sensors, it is demonstrated that the dynamics of passive silicone rubber strips located at a distance from the actuation point can be successfully exploited for computation through generalized synchronization realized via the medium of water. Future application scenarios are illustrated, in which the proposed technique is applied in emergency situations as a communication tool for transferring a message to a location that humans cannot easily access. For example, the technique could be applied to communicate with people trapped in submerged caves. Abstract : Herein, a method that exploits the dynamic coupling between soft structures and a water medium to allow for the transfer of computation to spatially distant locations is proposed. This technique is implemented by introducing a novel concept of self‐organized remote reservoirs that can autonomously alter their physical constituents in real time rather than using reservoirs with predefined, fixed physical constituents.